THE DEVELOPMENT OF TECHNICAL MATHEMATICS DIAGNOSTIC TEST FOR TECHNICAL EDUCATION STUDENTS AT RAJAMANGALA UNIVERSITY OF TECHNOLOGY KRUNGTHEP - Chiranorawanit, Sukit; Tantivitittapong, Ithinath (Journal of Social Science and Cultural, 2024)
The objective of this research was to: 1) create a diagnostic assessment to pinpoint areas of weakness in mathematical engineering disciplines for students enrolled in the Faculty of Industrial Education at Rajamangala University of Technology Krungthep and 2) assess the efficacy of the diagnostic test in finding deficiencies in learning particular mathematical engineering disciplines among students in the Faculty of Industrial Education at Rajamangala University of Technology Krungthep. This study was quasi-experimental research conducted on a sample group including 212 students from the Faculty of Industrial Education at Rajamangala University of Technology Krungthep. The research tools comprised a diagnostic test that serves as an illustrative and diagnostic tool for finding deficiencies in the comprehension of mathematical engineering courses. Both tests were in the format of multiple-choice questions. The first test aimed to gather information about misunderstandings in each topic, while the second test wss designed as a two-tiered diagnostic test, consisting of one correct option and three distractors. Data analysis was conducted by calculating the frequency percentages. The study’s results encompassed: the development of the diagnostic test for assessing deficiencies in understanding mathematical engineering topics commenced by gathering data through a 48-item illustrated examination. The gathered data were subsequently utilised to develop a two-tiered diagnostic examination featuring four multiple-choice alternatives, which were subjected to content validity assessments conducted by three experts. The diagnostic test administered to students in the Faculty of Industrial Education at Rajamangala University of Technology Krungthep to assess their proficiency in mathematical engineering subjects had difficulty indices ranging from 0.25 to 0.80, discrimination indices from 0.22 to 0.81, and a test reliability of 0.72. The test comprised 46 elements after undergoing quality inspections.